PENGARUH CSR, GCG, INFLASI TERHADAP PROFITABILITAS PADA PERUSAHAAN HIGH PROFILE DI INDONESIA - Dewi, Riana Rachmawati; Pitawati, Dian (Program Studi Akuntansi Fakultas Ekonomi Universitas Mahasaraswati Denpasar, 2018)
The problem presented in this research is how the influence that occurs between CSR, GCG, Inflation on profitability at companies that berkatagori high profile in Indonesia. The expected goal is to know CSR, GCG, Inflation on profitability measured using ROA, ROE, EPS and NPM ratio in high profile companies in Indonesia. This study has a population of 179 companies with high profile category in 2013-2015. Sampling using purposive sampling method. Testing of research hypothesis using multiple linear method. The results showed that Corporate Social Responsibility Disclosure does not affect profitability measured using ROA, ROE and NPM, whiÂle the disclosure of Corporate Social Responsibility affects the profitability measured using EPS. GCG measured by board size has an effect on profitability measured using ROA, ROE, EPS, and NPM. Inflation did not affect profitability. Disclo sure of CSR, GCG, and Inflation together affects profitability measured using ROA, ROE, EPS, and NPM.